Cyber Capacity-Building as a Geopolitical Tool: The Global North and Global South Relations in Contemporary Cyber Diplomacy - Urbanovics, Anna (POLARITIES, 2026)
Cyber diplomacy has become an important field, and one of the most efficient tools used by countries is cyber capacity building. This paper analyses these activities from the perspective of three key cyber diplomacy actors, the United Nations, the European Union, and the United States. As they follow different governance frameworks for cyber capacity building, the collaboration networks and regional focus of the projects they are involved in differ. This study uses a mixed methodology, combining descriptive statistics and network analysis. The analysis takes a data-oriented approach and data was gathered from the Cybil Portal. The results demonstrate that the United Nations has the most comprehensive network in terms of regional breakdown. The United States follows a great power logic, focusing on strategic regions. Meanwhile, the European Union is predominantly active in its neighborhood and plays an active role in promoting norms in these regions by its cyber capacity building engagements.